Variation in selenoenzyme genes and prostate cancer risk and survival. Issue 7 (9th November 2012) - Geybels, Milan S.; Hutter, Carolyn M.; Kwon, Erika M.; Ostrander, Elaine A.; Fu, Rong; Feng, Ziding; Stanford, Janet L.; Peters, Ulrike
Abstract: BACKGROUND: While several studies showed that selenium may prevent prostate cancer (PCa), few studies have evaluated variation in selenoenzyme genes in relation to PCa risk and survival. METHODS: We studied common variants in seven selenoenzymes genes in relation to risk of PCa and PCa‐specific mortality (PCSM). In a population‐based case–control study of men of European ancestry (1, 309 cases, 1, 266 controls), we evaluated 35 common, tagging single nucleotide polymorphisms (SNPs) in GPX1 (n = 2), GPX2 (n = 4), GPX3 (n = 6), GPX4 (n = 6), SEP15 (n = 4), SEPP1 (n = 6), and TXNRD1 (n = 7) in relation to PCa risk, and among cases, associations between these variants and risk of PCSM. We used logistic regression and Cox proportional hazards regression to estimate the relative risk of PCa and PCSM, respectively. RESULTS: Of the SNPs examined, only GPX1 rs3448 was associated with overall PCa risk with an odds ratio of 0.62 for TT versus CC (95% confidence interval, 0.44–0.88). SNPs in GPX2, GPX3, GPX4, SEP15, and SEPP1 had different risk estimates for PCa in subgroups based on stage and grade. We observed associations between SNPs in GPX4, and TXNRD1 and risk of PCSM. None of these associations, however, remained significant after adjustment for multiple comparisons. CONCLUSIONS: We found evidence that genetic variation in a subset of selenoenzyme genes may alter risk of PCa and PCSM. These results need validation in additional subsets. Prostate 73: 734–742, 2013. © 2012 Wiley Periodicals, Inc.